Consciousness and the Extended Mind in the "Metamodernist" Novel. Issue 7 (3rd October 2018) - Lavery, Nick
ABSTRACT: This article argues that Ali Smith's How to be Both (2014) and Will Self's Umbrella (2012) can be read as employing a metamodernist approach to the depiction of subjective consciousness. The article looks at how both novels follow on from their authors' engagement with recent advances and debates in philosophy of mind. This engagement results in an implicit model of the mind as extended in both novels. Drawing on work on the relationship between cognition and affect, the article argues that this model of the mind can be understood in terms of an oscillation at the level of consciousness. This article proposes that oscillation is a dynamic fundamental to the mind as depicted in these novels, allowing it to connect the metamodernist framework with contemporary philosophy of mind.